Differences in CEA Levels and Nutritional Status in Stage III Rectal Cancer Patients Undergoing Different Types of Therapy - Rizky, Abdullah; Mahendra, Vito; Chodidjah, Chodidjah (CV. Dyoqu Publishing Management, 2025)
Background: Rectal cancer is a type of malignancy with a higher rate of local recurrence compared to colon cancer. Various therapies such as surgery, chemotherapy, and radiotherapy are commonly used for treatment. Monitoring the effectiveness of these therapies can be supported by clinical parameters such as Carcinoembryonic Antigen (CEA) levels and nutritional status measured by Body Mass Index (BMI). Aims: This study aimed to examine the differences in CEA levels and nutritional status among rectal cancer patients receiving different types of therapies. Methods: This was an observational analytic study with a cross-sectional design. The sample consisted of 56 patients with stage III rectal cancer at Sultan Agung Islamic Hospital Semarang during the period of 2018-2024. Data were collected from medical records and included patients who received either surgery + chemotherapy (n = 33) or surgery + chemotherapy + radiotherapy (n = 23). CEA levels were analyzed using the Mann-Whitney U test, and nutritional status was analyzed using the Independent Sample T-Test. Result: The results showed no statistically significant difference in CEA levels between the two therapy groups (p = 0.405). However, a significant difference was found in nutritional status, with patients undergoing radiotherapy showing lower BMI values compared to those without radiotherapy (p = 0.000). Conclusion: CEA levels did not significantly differ between types of therapy in stage III rectal cancer patients. However, radiotherapy was associated with a significant decline in nutritional status. These findings highlight the importance of integrating nutritional monitoring in the management of rectal cancer patients receiving combined therapy